Only Yesterday : An Informal History of the Nineteen-Twenties - Allen, Frederick Lewis, 1890-1954 (New York Batman Books, 1952)
A social history of the United States during the "roaring twenties." Examines American individualism and the decade that they knew Mah Jong and Mencken, Couéism and Coolidge, Listerine and Lindbergh, as well as Capone, Ford, Babe Ruth, the Teapot Dome, and bathtub gin.
Include Appendix and Index
Keywords: United States -- Social conditions